ORIENTASI REKAHAN PADA SUMUR INJEKSI SUATU FAKTOR PENTING UNTUK PENGEMBANGAN LAPANGAN DENGAN WATERFLOOD (STUDI KASUS LAPANGAN X-ASAMERA) - Suzandi, Edwil
Some efforts have been done to maintain rate of oil production. Waterflood technology using water injection wells will be able to increase oil recovery factor. The orientation of fluid injection movement could be predicted by fracture orientation in the waterflooding field. The fracture orientation is very useful to determine the suitable pattern of injection considering the sweep efficiency and recovery of oil. This method is used to determine fracture orientation including the injectivity test and hall plot curve analysis. Fracturing pressure and injection rate used to analyze the process of water injection which were taken from injectivity test. Hall plot technique will analyze fracturing pressure from injectivity test with evaluation the preference of curve gradient. Fracturing gradient will give the possibility of fracture orientation. The method of this study was applied in X Asamera field. From this method, it will be able to determined fracture orientation happened and help for evaluating the injection fluid. Waterflood field development strategy is designed by considering the change of injection pattern which suitable with fluid injection orientation.